Artefacts, and Taking on a Religious Variation - Arzroomchilar, Ehsan (Journal of Human-Technology Relations, 2025)
Artefacts mediate human perception and behaviour for sure, but what is less clear is the way their mediation is exerted. The reason for the ambiguity lies partially in the fact that artefacts work differently in different contexts. Ihde has invented the term multistability to address this characteristic inherent to artefacts. So, there might be various types of mediation conceivable based on such a multitude of stabilities a given artefact could take on. In this article, I try to shed some light on the phenomenon of multistability to see how particularly religious stability may emerge from an otherwise profane artefact. To that end, I will place my focus on the tradition of Islamic calligraphy and the pivotal role reed pens have played in it and explore accordingly how both secular and religious stability might arise from the seemingly same physical object. To that purpose, I will suggest drawing on MacIntyre’s views on three notions of practice, narrative, and tradition, and will argue that these three notions may spotlight how an artefact could receive varying stabilities.